2020
DOI: 10.1111/ejn.14759
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural effects of extracellular matrix protein Fras1 depletion in the mouse

Abstract: Fras1 is an extracellular protein of the basement membranes that surround embryonic epithelia, choroid plexuses and meninges in foetal mouse brain. Depletion of Fras1 in knockout mice results in sub-epidermal blistering and fusion of eyelids and digits as well as malformation of lungs and kidneys. Mutations in the human counterpart FRAS1 are responsible for the Fraser Syndrome with clinical manifestations similar to the murine phenotype. In addition, brain deformities or mental impairments have occasionally be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 59 publications
(73 reference statements)
0
11
0
Order By: Relevance
“…They provide insights into the interplay between the major ECM proteins and the intracellular Tau levels, and demonstrate a direct effect of aggrecan on Tau expression and phosphorylation. Kalpachidou et al (2020) describe the behavioral phenotype of mice deficient in Fras1, an extracellular protein of the basement membranes that surround embryonic epithelia, choroid plexuses and meninges in fetal mouse brain. Mutations in human Fras1 are responsible for the Fraser Syndrome with brain deformities and mental impairments occasionally observed in patients.…”
Section: Brain Extracellular Matrix: An Upcoming Target In Neurological and Psychiatric Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…They provide insights into the interplay between the major ECM proteins and the intracellular Tau levels, and demonstrate a direct effect of aggrecan on Tau expression and phosphorylation. Kalpachidou et al (2020) describe the behavioral phenotype of mice deficient in Fras1, an extracellular protein of the basement membranes that surround embryonic epithelia, choroid plexuses and meninges in fetal mouse brain. Mutations in human Fras1 are responsible for the Fraser Syndrome with brain deformities and mental impairments occasionally observed in patients.…”
Section: Brain Extracellular Matrix: An Upcoming Target In Neurological and Psychiatric Disordersmentioning
confidence: 99%
“…Kalpachidou et al. (2020) describe the behavioral phenotype of mice deficient in Fras1, an extracellular protein of the basement membranes that surround embryonic epithelia, choroid plexuses and meninges in fetal mouse brain. Mutations in human Fras1 are responsible for the Fraser Syndrome with brain deformities and mental impairments occasionally observed in patients.…”
mentioning
confidence: 99%
“…Additionally, HLA-DQA1 and INPP5D are expressed in dendritic cells and monocytes and involved in immune processes, and the migration of monocytes across an inflamed BBB can cause differentiation into dendritic cells [47]. FRAS1 was significantly downregulated in AD compared to controls in blood from ε3/ε4 AD individuals and a recent study showed that FRAS1 knockdown mice were impaired in memory and learning behaviors [48].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, HLA-DQA1 and INPP5D are expressed in dendritic cells and monocytes and involved in immune processes, and the migration of monocytes across an inflamed BBB can cause differentiation into dendritic cells [42]. FRAS1 was significantly downregulated in AD compared to controls in blood from ε3/ε4 AD individuals and a recent study showed that FRAS1 knockdown mice were impaired in memory and learning behaviors [43].…”
Section: Discussionmentioning
confidence: 99%